Kalkulasi Sisa Emisi Co2 UIN Walisongo Semarang Sebagai Landasan Mewujudkan Pengurangan Carbon Footprint Kampus Berkelanjutan - Noor Amalia Chusna; Nibras Cahya Dirgantara (Interdisciplinary Social Studies, 2025)
The reduction of carbon dioxide (CO?) emissions at UIN Walisongo Semarang is a strategic step toward achieving a sustainable campus. This article examines the calculation of residual CO? emissions as a foundation for reducing the carbon footprint at UIN Walisongo Semarang, with a focus on the role of green open spaces in carbon sequestration. The research combines an analysis of CO? emissions from motor vehicles, energy consumption, and building operations, as well as the role of open spaces in carbon storage through photosynthesis and evapotranspiration. The analysis results show that although 82% of the campus area is dedicated to open spaces, CO? emissions remain high, with a 5.3% increase in the carbon footprint from 2020 to 2021. The calculation of residual CO? emissions reveals the significant potential of open spaces in reducing the carbon footprint; however, additional efforts are needed to manage emissions effectively in order to achieve a more environmentally friendly campus. This study provides recommendations for managing open spaces as a climate change mitigation solution at the university.